Community and Peer Learning Approaches for Teaching Chemistry to Out-of-School Children in Zaria Educational Zone - Muhammad-Lawal, Hadiza; Muhammad, Madaki Saadatu; Ahmad, Ismail (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The research examines the effects of teaching chemistry to out of-school children in Zaria educational zone through the use of peer-based and community-based learning strategies. This was done to lower the community's out-of-school children population. The study used a single-group pretest-posttest quasi-experimental research design. 545 community out-of-school children in Zaria Education Zone, ages 14 to 16, make up the study's population. Using the purposive sample approach, 50 children were chosen. Data for this research were gathered using a chemistry performance test with a reliability coefficient value of 0.79. Using an independent one-sample t-test, the research hypothesis, which states that a significant difference does not exist between the performance in chemistry among participants before and after being exposed to community and peer-based learning strategies in teaching chemistry concepts, was tested using an independent t-test. The results showed that when participants were taught chemistry using community and peer-based learning techniques, there was a significant change in their performance. The results led to the following recommendations: knowledgeable individuals in a community should act as mentors to encourage out-of-school children to return to school by giving presentations and participating in community development initiatives.